2006
DOI: 10.1515/hf.2006.039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of NAEM salt-catalyzed alcohol organosolv pulping as a biorefinery

Abstract: Characteristics of the NAEM wneutral alkali-earth metal; CaCl 2 and Mg(NO 3 ) 2 in this studyx salt-catalyzed alcohol organosolv pulping of softwood were investigated and compared to AlCl 3 -catalyzed kraft pulping. The catalysts control the acidity of the cooking liquor, which is the key factor for pulping selectivity and fiber separation. The crucial role of catalysts in alcohol organosolv pulping is demonstrated. The pulp yield and quality were satisfactory. The dissolved wood components in the spent liquor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Alternatively, pretreatment under alkaline conditions, such as ammonia fiber explosion and lime pretreatment, results in extensive delignification while preserving a greater amount of hemicellulose in the solid fraction, which may require the addition of hemicellulosic enzymes [4,18]. Moreover, it may also be advantageous to consider the use of neutral alkaline earth metal (NAEM) salt catalysts, such as AlCl 2 and MgCl 2 , as previous studies [20,21] have shown that organosolv pulping using MgCl 2 resulted in the partial preservation of hemicellulose in the solid fraction and comparable delignification when compared to the use of an acid catalyst such as H 2 SO 4 . Although studies with alternative catalysts have focused mostly on the optimization of pulps for papermaking, they may also be useful for creating substrates with varying characteristics and in limiting the formation of sugar degradation products such as furfurals and organic acids [22].…”
mentioning
confidence: 99%
“…Alternatively, pretreatment under alkaline conditions, such as ammonia fiber explosion and lime pretreatment, results in extensive delignification while preserving a greater amount of hemicellulose in the solid fraction, which may require the addition of hemicellulosic enzymes [4,18]. Moreover, it may also be advantageous to consider the use of neutral alkaline earth metal (NAEM) salt catalysts, such as AlCl 2 and MgCl 2 , as previous studies [20,21] have shown that organosolv pulping using MgCl 2 resulted in the partial preservation of hemicellulose in the solid fraction and comparable delignification when compared to the use of an acid catalyst such as H 2 SO 4 . Although studies with alternative catalysts have focused mostly on the optimization of pulps for papermaking, they may also be useful for creating substrates with varying characteristics and in limiting the formation of sugar degradation products such as furfurals and organic acids [22].…”
mentioning
confidence: 99%
“…Here, aggressive catalyst acids at high concentrations (see Supplementary Information Tab. S2) probably hydrolyze and/or degrade sugars as has been observed for spruce, which was extensively disintegrated after organosolv pretreatment [49]. Nevertheless, it seems that for most experimental conditions, glucose (i.e., cellulose) stays in the recovered fraction.…”
Section: Analysis Of Recovered Materialsmentioning
confidence: 80%
“…So, the amount of lignin removal after alkaline pretreatment was more than that after treatment with acidic and neutral sulfite. During the ethanol sulfite pretreatment, the surface tension reduced because of the addition of ethanol, which was a benefit of solution penetration and lignin sulfonation, resulting in more lignin removal [17-19]. Moreover, the boiling point of ethanol is lower than that of water; hence, the pressure in the ethanol sulfite pretreated bottle was the highest.…”
Section: Resultsmentioning
confidence: 99%